Shrimp miR-12 Suppresses White Spot Syndrome Virus Infection by Synchronously Triggering Antiviral Phagocytosis and Apoptosis Pathways - Shu, Le; Zhang, Xiaobo (Frontiers in Immunology, 2017)
Growing evidence has indicated that the innate immune system can be regulated by microRNAs (miRNAs). However, the mechanism underlying miRNA-mediated simultaneous activation of multiple immune pathways remains unknown. To address this issue, the role of host miR-12 in shrimp (Marsupenaeus japonicus) antiviral immune responses was characterized in the present study. The results indicated that miR-12 participated in virus infection, host phagocytosis and apoptosis in defense against white spot syndrome virus (WSSV) invasion. MiR-12 could simultaneously trigger phagocytosis, apoptosis and antiviral immunity through the synchronous downregulation of the expression of shrimp genes [PTEN (phosphatase and tensin homolog) and BI-1(transmembrane BAX inhibitor motif containing 6)] and the viral gene (wsv024). Further analysis showed that miR-12 could synchronously mediate the 5’-3’ exonucleolytic degradation of its target mRNAs, and this degradation terminated in the vicinity of the 3’ untranslated region (3’UTR) sequence complementary to the seed sequence of miR-12. Therefore, the present study showed novel aspects of the miRNA-mediated simultaneous regulation of multiple immune pathways.